Standard and direct costing - Gillespie, Cecil (New Delhi : Prentice-Hall of India private Limited, 1962)
The purpose of this book is to explain the three fundamental methods of operating standard costs and to demonstrate the application of standard costs to direct costing.
"Former title: Accounting procedure for standard costs."
Includes bibliographical references and index.
hza 05/10/2018
Loans
Keywords: Cost accounting; Factories; Manufactures